2013
DOI: 10.1039/c3sm50901j
|View full text |Cite
|
Sign up to set email alerts
|

Precise determination of the Poisson ratio in soft materials with 2D digital image correlation

Abstract: In this article, we demonstrate the application of digital image correlation (DIC) in evaluating the strains and Poisson ratio of a range of soft materials in terms of their spatial and temporal resolutions. Four samples of Polydimethylsiloxane (PDMS) were used as control substances and were measured to have Poisson ratios of 0.498, 0.503, 0.500, and 0.499, in agreement with the reported incompressible value of 0.50 [1]. Two carbon nanotube (CNT) elastomers of identical composition, but one of a homogeneous an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
114
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 184 publications
(121 citation statements)
references
References 38 publications
5
114
0
2
Order By: Relevance
“…A good agreement between the nominal and the measured shear moduli of polyacrylamide films is obtained for a Poisson coefficient of 0.43 ± 0.01. This value is consistent with the experimental measurements on polyacrylamide gels, whose Poisson coefficient ranges from 0.25 (theoretical value [25]) to 0.5 according to the method and the timescale of the measurements [26,27]. In conclusion, we observed that PA gels respond to the dextran pressure as they would do in case for a pure mechanical pressure.…”
Section: Discussionsupporting
confidence: 91%
“…A good agreement between the nominal and the measured shear moduli of polyacrylamide films is obtained for a Poisson coefficient of 0.43 ± 0.01. This value is consistent with the experimental measurements on polyacrylamide gels, whose Poisson coefficient ranges from 0.25 (theoretical value [25]) to 0.5 according to the method and the timescale of the measurements [26,27]. In conclusion, we observed that PA gels respond to the dextran pressure as they would do in case for a pure mechanical pressure.…”
Section: Discussionsupporting
confidence: 91%
“…To map the evolution of strain in the tensile tests with a high degree of accuracy, DIC was performed using the Vic 2D software from Correlated Solutions, Inc. This method is well known for its high resolution, 37 and was recently used to determine the moduli (elastic and shear), 38 and Poisson ratios, 38,39 of low V f ( 1 vol. % CNTs) polymer composites.…”
Section: B Mechanical Testingmentioning
confidence: 99%
“…The viscoelastic anisotropic rubber studied experimentally has a low anisotropy, therefore, in the numerical calculations, the Poisson's ratio was assumed to be the same in all directions and similar to isotropic rubbers (ν ¼ 0:45). However, the exact Poisson's ratio might be different at different directions (as mentioned in Section 2.1) which can be accurately measured by novel methods [41]. Not precise determination of the Poisson's ratio might result in a disagreement between the model and the experiments for a material with high anisotropy.…”
Section: Discussionmentioning
confidence: 98%